PENGEMBANGAN BUKU DIGITAL SEBAGAI MEDIA UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IV - Hiwa Wonda; Martha K. Kota; Chikita Dina Arianti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article reports the development of a digital book as media to increase fourth-grade elementary school students’ learning motivation in the learning theme 4 sub-theme 2. The research is a development research method with a 4D design (Define, Design, Development, Dissemination) and one group pretest-posttest developmental model. Based on the SBI analysis, the developed digital book developed obtained 4,57, which is in the very feasible category. After using digital books, students’ learning motivation increased to 9.74%. The effectiveness of these digital books in increasing students’ learning motivation after being analyzed is 60.59%, which is categorized as quite effective. It is supported by asignificant percentage in student learning outcomes is 10.96% with a significant value of 0,223. The development of sophisticated technology increasingly should also be updated in the educational context. By utilizing technological development, teachers can design a digital book that can be used as learning media and teaching materials that can be used during teaching and learning activities or used out of the classroom. Digital books are also equipped with animations, videos, and voice recordings so that students can learn independently and have the same learning experience. As regards this, conventional books should be designed innovatively and developed based on technological developments in order to make them more practical, interesting, and able to create a pleasant learning atmosphere. Hence, students can generate and increase their learning motivation.